Media narratives of kindness − a critique. (November 2020) - Dutta, Mohan; Elers, Phoebe
Since the coronavirus outbreak, various media outlets across the globe have disseminated and promoted stories of kindness as registers for COVID-19 response. These narratives of kindness appeal to the human capacity to do good, inviting the public to 'make a difference' by performing altruistic acts of helping those who are less fortunate or in a time of need. However, there is a dark side to these narratives, one that does not serve those who are precarious, underprivileged or marginalised, by obfuscating and erasing necessary conversations on the transformative policies and infrastructure changes needed to address fundamental structural issues underlying the deep inequalities we inhabit in a COVID world.